CPA Examination: Auditing. - Meigs, Walter B. (The Accounting Review, 1966)
The article presents problems and their solutions prepared by the Board of Examiners of the American Institute of Certified Public Accountants, for the auditing section of the November 1965 Uniform Certified Public Accountants examination held on November 04, 1965. The first question deals with auditing procedures to be followed for auditing of a shopping center with 30 store tenants, and the preparation of an auditor's report under certain given conditions. All leases with these store tenants provide for a fixed rent plus a percentage of sales, net of sales taxes, in excess of a fixed dollar amount computed on an annual basis. Each lease also provides that the landlord may engage a certified public accountant to audit all records of the tenant for assurance that sales are being property reported to the landlord. The second question deals with the issue of auditing financial statements that have been prepared using electronic data processing equipment, and the accountant has found that his traditional audit trail has been obscured.